(NpRINCIP KONWERGENCII ANALIZATORNYH SISTEM (B/s - (NaJRAPETXQNC(B, (N|RWAND {AMIROWI^s; (NbATUEW(B, (NaLEKSANDR sERGEEWI^s; (NoB_EDINENNYJ NAU^NYJ SOWET (B"(NfIZIOLOGIQ ^ELOWEKA I VIWOTNYH(B" (NaKADEMII nAUK sssrs ((NlENINGRAD (B:s (NnAUKA(B,s, 1969)
(NrEZ@ME NA ANGL(B. (NQZ(B. : (NS(B. 81-83s
(NbIBLIOGR(B. 330 (NNAZW(B.s
Keywords: (NnERWNAQ SISTEMA (B((NFIZIOLOGIQ(B)s